Co-evolution of NK receptors and HLA ligands in humans is driven by reproduction - Moffett, Ashley; Colucci, Francesco (Immunological reviews, 2015)
Summary Allogeneic individuals co‐exist during pregnancy in eutherian mammals. Maternal and fetal cells intermingle at the site of placental attachment in the uterus, where the arteries are remodeled to supply the fetus with oxygen and nutrients. This access by placental cells to the maternal supply line determines the growth and birth weight of the baby and is subject to stabilizing selection. Invading placental trophoblast cells express human leukocyte antigen class I ligands (HLA‐E, HLA‐G, and HLA‐C) for receptors on maternal uterine natural killer (NK) and myelomonocytic cells, CD94/NKG2, leukocyte immunoglobulin‐like receptor (LILR), and killer immunoglobulin receptor (KIR). Of these, only the KIR/HLA‐C system is highly polymorphic. Different combinations of maternal KIR and fetal HLA‐C variants are correlated with low birth weight and pre‐eclampsia or high birth weight and obstructed labor, the two extremes of the obstetric dilemma. This situation has arisen because of the evolution of bipedalism and subsequently, in the last million years, larger brains. At this point, the human system began to reach a balance between KIR A and KIR B haplotypes and C1 and C2 epitopes of HLA‐C alleles that reflects a functional compromise between the competing demands of immunity and reproduction.